Impact of an Ageing Society on Healthcare Expenditure of National Health Insurance in Taiwan - Karina Agustin; Shou-Yan Chou (Jurnal Teknik Industri, 2019)
The increase in healthcare expenditure always becomes an issue considered by the National Health Insurance (NHI) program in Taiwan. Accordingly, analyzing the root cause is a significant first step in dealing with this issue. This study hypothesized that the greying population in Taiwan is the main reason that devours a vast health care expenditure. Samples of the population in Taiwan's National Health Insurance databases together with age-expenditure profile analysis and decomposing approach of the components of healthcare expenditure will analyze the impact of population ageing and estimate the contributions of population ageing shifting to NHI's expenditure in Taiwan.  The result could be considered for policymakers and the government to overcome this issue in Taiwan.